Potential Application of Camel Milk as a Therapeutic Ingredient in Bath Soaps and Shampoos - Elly Oginga; Julius Toeri; Eunice Marete; Joshua Arimi (Dermatology Research and Practice)
The increasing worldwide market for natural-ingredient-based cosmetic toiletries is fuelled by the awareness of the dangers of synthetic cosmetics and benefits of natural-based cosmetics on the skincare and management of skin disorders. Besides naturally formulated cosmetics being biodegradable, they also contain ingredients which are chemically beneficial to human skin. Milk-based cosmetics are very promising since milk is rich in essential components such as lactoferrins, vitamins, and lactic acids, which have shown therapeutic properties against disorders such as skin cancer, acne scars, and dandruff. One of the milk that is very promising in the cosmetics industry is the camel milk. Currently, there is limited information in literature regarding the use of camel milk in cosmetics and their benefits. Camel milk stands out from bovine milk following its unique therapeutic properties and chemical composition, making it a potential ingredient for skincare and haircare products such as bath soaps and shampoos. The aim of this paper is to review the available literature on camel milk composition and evaluate the contribution of camel milk constituents to cosmetics.